Features of 'talent-branding' at the University of Pécs - Balogh Gábor; Principles of Scientific Management : International Scientific Conference Szeged 2011 (University of Szeged Faculty of Economics and Business Administration Szeged, 2013)
This paper deals with the particular issues of nurturing of talent at the University of Pécs. Institutes, students and employers together are united in the sense that all three search for talented individuals, even if, in other respects, their motivation, goals and methods differ. In this study I analyse features of student ‘self-branding’. One necessary feature of a company is to act as a ‘talent-magnet’, and so companies should aim to attract skilled employees using the best marketing tools. The empirical study is based on questionnaires referring to experience in professional practice (2009-2011). The data apply to a total of 737 students. One of the most important features of the study was to emphasise regional characteristics, the result of which was that the most recent data focused strongly on Pécs and Budapest. Significant differences were found in students’ skills in the two cities, these being most visible as basic methodological skills, professional concepts, discipline and responsibility.
Keywords: Társadalomtudományok; Oktatástudomány